The Rise of the Latino Vote A History - Francis-Fallon, Benjamin 1979- (Harvard University Press, 2019)
Francis-Fallon returns to the origins of the U.S. "Spanish-speaking vote" to understand the history and potential of this political bloc. He finds that individual voters affiliate more with their particular ethnic communities than with the pan-ethnic Latino identity created for them, complicating the notion of a broader Latino constituency